2009
DOI: 10.1186/1476-511x-8-60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperlipidemia on the expression of circadian genes in apolipoprotein E knock-out atherosclerotic mice

Abstract: BackgroundCircadian patterns of cardiovascular vulnerability were well characterized, with a peak incidence of acute myocardial infarction and stroke secondary to atherosclerosis in the morning, which showed the circadian clock may take part in the pathological process of atherosclerosis induced by hyperlipidemia. Hence, the effect of hyperlipidemia on the expression of circadian genes was investigated in atherosclerotic mouse model.ResultsIn apoE-/-mice on regular chow or high-fat diet, an atherosclerotic mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Metabolic disorders including dyslipidaemia and diabetes are epidemiologically linked to AD38. High-fat diets are known to alter both the central and peripheral clocks, including the locomotor activity1139. Hypothetically, the elevated cholesterol levels in ApoE −/− mice could reset the SCN central clock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic disorders including dyslipidaemia and diabetes are epidemiologically linked to AD38. High-fat diets are known to alter both the central and peripheral clocks, including the locomotor activity1139. Hypothetically, the elevated cholesterol levels in ApoE −/− mice could reset the SCN central clock.…”
Section: Discussionmentioning
confidence: 99%
“…The clock and atherosclerosis-related genes were found differentially expressed in ApoE −/− mice. For example, ApoE −/− mice showed phase delay in the circadian pattern of serum lipid levels11, altered expression of clock12 and atherosclerosis/thrombosis-related genes13.…”
mentioning
confidence: 99%
“…So circadian rhythm disorder of these CCGs in PVSMCs should be attributed to the attenuation expression of clock genes we reported previously. Previous studies have confirmed that the hyperlipidaemia could impair the circadian clock in vivo and in vitro [6, 26]. Especially Chen S et al [6] showed that the free fatty acids (FFAs) could inhibit the clock genes expressions in contractile VSMCs via the suppression of Smarcd1.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral circadian clock profiles have been increasingly recognized as important players in tissue physiology. Recent studies have indicated that hyperlipidaemia reduces amplitudes and perturbs the periodicity of clock genes in cardiovascular and hepatic tissues in apoE ‐deficient mice . In humans, SNPs in the Per2 locus functionally intersected with total fasting saturated fatty acid levels to modulate circulating apoC‐II and apoB‐48, which is relevant to the dyslipidaemia of metabolic syndromes .…”
Section: Discussionmentioning
confidence: 99%